Pengembangan Media Pembelajaran Berbasis Augmented Reality pada Materi Bangun Ruang di Kelas I SD - Mardiana, Ana; Abidin, Yunus (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
Education in the era of the Industrial Revolution 4.0 is an education that highlights the use of digital technology in the learning process. Teachers or students are required to be able to improve their competence and skills. Digital technology in education is one reason teaching and learning activities should be supported to be more effective, efficient, and fun. This research aims to describe the development of augmented reality-based learning media on building materials in grade 1 elementary school, describe the design of augmented reality–based learning media as a solution to problems, describe the feasibility and testing requirements for the product that, and describe the final product of augmented reality – based learning media. The research used the Design-Based Research (DBR) research and development method using the Reeves model research stages, that is: 1) identification and analysis of problems; 2) develop solutions; 3) carry out an iterative process 4) reflection. The data collection technique is through data collection using preliminary studies and field studies. The instruments used in this research are interview instruments, expert judgment, questionnaires, and documentation. Based on the research results at SDN Sukarame, Tasikmalaya Regency, research data showed that the augmented reality–based learning media developed was suitable for use in learning. Feasibility is demonstrated from validation results by expert validators, and usability is demonstrated from the results of trials that have been carried out. So, based on the results of this research, the development of augmented reality–based learning media on spatial building materials can be used as an alternative media in learning in grade 1 elementary school.